2020
DOI: 10.1177/0950422220919655
|View full text |Cite
|
Sign up to set email alerts
|

A critical perspective on industry involvement in higher education learning: Enhancing graduates’ knowledge and skills for job creation in Nigeria

Abstract: This study explores how Nigerian higher education institutions can facilitate industry involvement in the design of programmes and activities that enhance the development of students’ knowledge and skills for business start-ups, leading to job creation. Using interview and focus group methodologies, the researchers obtained rich information from 50 participants, including higher education teachers, final year undergraduate students who had taken part in the compulsory Student Industrial Work Experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 39 publications
3
36
0
Order By: Relevance
“…It provides deeper insights into how IIHEL might engender positive job creation intention among undergraduate students, and so ultimately improve business start-up intention and behaviours -the former being a fairly neglected domain in industry and higher education research. The authors acknowledge previous research showing that IIHEL can provide various benefits (e.g., Okolie et al, 2020a;Dickinson and Griffiths, 2017); yet, the direct implications for student job creation intention are not fully understood. Our study addresses an important research gap, highlighting useful ways to develop students' job creation intention and improve higher education-industry partnerships to improve the quality of graduate outcomes.…”
Section: Insert Figure 1 About Herementioning
confidence: 84%
See 1 more Smart Citation
“…It provides deeper insights into how IIHEL might engender positive job creation intention among undergraduate students, and so ultimately improve business start-up intention and behaviours -the former being a fairly neglected domain in industry and higher education research. The authors acknowledge previous research showing that IIHEL can provide various benefits (e.g., Okolie et al, 2020a;Dickinson and Griffiths, 2017); yet, the direct implications for student job creation intention are not fully understood. Our study addresses an important research gap, highlighting useful ways to develop students' job creation intention and improve higher education-industry partnerships to improve the quality of graduate outcomes.…”
Section: Insert Figure 1 About Herementioning
confidence: 84%
“…This is an important empirical and theoretical gap that the present study intends to explore systematically. This study draws on that of Okolie et al (2020a) which identifies factors that contribute to students' knowledge and skill development, and includes recommendations for (i) curriculum restructuring, (ii) renewed pedagogical approaches and competencies (REPAC), (iii) building effective linkages between higher education and industry (BELHI), and (iv) career training and mentoring (CTM) as effective practices for IIHEL. The goal of the present study is to determine how each of these four constituents of the recommended framework for IIHEL might boost student job creation intention and the mechanisms through which IIHEL might influence student job creation intention.…”
mentioning
confidence: 99%
“…The study recommended that government make policies that will guarantee students' right placement in the right industry. Knouse et al (2008) amd Okolie et al (2021) also identified the relationship between participation in an internship and subsequent job placement. The study surveyed students at graduation and then six months later to examine the variables under study.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Obviously, students amass a wealth of work experience from an internship (Okolie et al, 2021;Binder et al, 2015). Another angle is employers' benefits resulting from employing interns who are young fresh and of the first choice to work with (Kysor and Pierce, 2000;Mamaleka, 2020).…”
Section: Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation